2014
DOI: 10.3892/or.2014.3668
|View full text |Cite
|
Sign up to set email alerts
|

HOXA7 stimulates human hepatocellular carcinoma proliferation through cyclin E1/CDK2

Abstract: HOX genes are transcription factors that control morphogenesis, organogenesis and differentiation. Increasing evidence suggests that HOX genes play a role in hepatocellular carcinoma (HCC) progression; however few studies have defined the functional roles and mechanisms of action. In the present study, we used siRNA and forced-expression in multiple cell lines to define the role of HOXA7 in the regulation of proliferation of HCC in vitro and in vivo. Knockdown of endogenous HOXA7 decreased the proliferation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Recently, an increasing number of studies have indicated that HOX genes play important roles in oncogenesis [2325]. Many cancers exhibit altered HOX gene expression, particularly leukemia, breast, prostate and lung carcinomas [2630].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of studies have indicated that HOX genes play important roles in oncogenesis [2325]. Many cancers exhibit altered HOX gene expression, particularly leukemia, breast, prostate and lung carcinomas [2630].…”
Section: Discussionmentioning
confidence: 99%
“…Many cancers exhibit altered HOX gene expression, particularly leukemia, breast, prostate and lung carcinomas [2630]. It has been reported that HOXA7 stimulates human hepatocellular carcinoma proliferation through cyclin E1/CDK2 [25]. However, the specific functional role of HOXA7 in liver cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclins act as (i) regulators of specific kinases and (ii) contribute to the coordination of mitotic events. In many tumors overexpression of this gene has been observed 112 . It was recently shown that proliferation of 3T3-L1 preadipocytes promoted by recombinant myostatin increased expression of proliferation related genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of HOXA7 mRNA is higher in epithelial ovarian cancer than in benign tumors (10), and HOXA7 antibody in serum can be applied for diagnosis of ovarian epithelial cancer (17). HOXA7 also stimulates human hepatocellular carcinoma proliferation through regulation of cyclin E1/CDK2 (18). In addition, HOXA7 has been reported to regulate the differentiation of promyelocytic leukemia (19).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we infer that the HOXA7 gene can serve as an independent tumor growth factor in several types of cancer. Li et al (18) have reported that HOXA7 might stimulate hepatic carcinoma by promoting the expression of cell cycle protein E1/CDK2. In addition, HOXA7 has been considered an important target for methylation, which initiates tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%